PENGARUH PENGETAHUAN DAN SIKAP TERHADAP PERILAKU MASYARAKAT PADA BANK SYARIAH DI WILAYAH KELURAHAN SEI SIKAMBING D - Dewi Rafiah Pakpahan (Universitas Islam Negeri Sumatera Utara, 2017)
Islam has set up all human behavior in fulfilling the needs of his life that is does not deviate from the teachings of Islam. Different reactions will describe different behavior that is different then the consumer will give different reaction in terms of feelings toward the same information. The purpose of the study is to know the influence of the knowledge and attitude toward the behavior of the community in the Islamic bank. This research is a research field that uses a quantitative approach. The population of the research was the head of the family in Kelurahan Sei Sikambing D totalling 297 and sample as many as 59 respondents. The results of the research there were obtained: the influence of knowledge (p = 0.001); attitude (p = 0.000) of community behavior on Islamic banks; and there is the influence of the knowledge and attitude to behavior society in Islamic banks (p = 0.000). Conclusions: knowledge of Islamic banks which received the community cannot materialize if it does not have a good attitude so as not to be embodied into action is customer into Islamic banking which is a form of behavior.